Gambling: A Unique Policy Challenge - Robert I. Simpson (Law & Governance, 2017)
[This article was originally published in Healthcare Quarterly, 15(4)] Over the past 15 years, provincial governments across Canada have consistently demonstrated their willingness to expand the availability of gambling (Campbell et al. 2010). Most recently, the Ontario Lottery and Gaming Corporation (OLG) unveiled expansion plans that included eliminating 17 slots-at-race track venues and replacing them with 29 casinos nested more closely to population centres. The singular driving force for expansion is government's quest for non-tax revenue, largely in response to an ideologically based disaffection for tax increases. The trade-off is that, without precedent, government becomes directly involved in providing an activity that knowingly harms the population it is elected to serve. This fact alone demands unique policy consideration in relation to how government implements and manages its gambling agenda (Smith and Rubenstein 2009). Using the current Ontario initiative as a case in point, this article explores several of these considerations.
Keywords: Gambling is addictive. As with drinking, gambling involvement occurs along a continuum from problem free, at one extreme, to very harmful at the other. Unique to gambling, however, is that the harm can include extreme financial duress that may profoundly affect family well-being over the long term, if not permanently.